Analisis Laporan Realisasi Anggaran untuk Menilai Kinerja Keuangan Pemerintah Provinsi DKI Jakarta Tahun 2021-2024: Analysis of the Budget Realization Report to Assess the Financial Performance of the DKI Jakarta Provincial Government for 2021-2024 - Amelia Sabila; Mutia Zahra; Najwa Nabila; Yuni Artika sari; Azzhara Maya Cessy; Ghurhanawan Ghurhanawan (CV Warnak Johanna Nusantara, 2026)
This study is based on the importance of evaluating local government financial performance to assess the effectiveness of Regional Original Revenue (PAD) management and the efficiency of budget utilization as a form of public financial accountability. This study aims to analyze the financial performance of the DKI Jakarta Provincial Government based on the Budget Realization Report (LRA) for the 2021–2024 period. The research employed a descriptive quantitative method using secondary data obtained from the Budget Realization Reports of the DKI Jakarta Provincial Government. The analysis focused on regional revenue and expenditure realization, the effectiveness ratio of Regional Original Revenue (PAD), and the regional financial efficiency ratio. The results indicate that the financial performance of the DKI Jakarta Provincial Government was generally in good condition. The PAD effectiveness ratio showed favorable results, reaching 92.09% in 2021, 81.94% in 2022, 101.44% in 2023, and 100.55% in 2024, indicating effective to highly effective performance. Meanwhile, the regional financial efficiency ratio ranged from 93.96% to 96.40%, indicating that financial management was still categorized as less efficient. These findings suggest that regional revenue management has been optimized; however, greater efforts are still needed to improve the efficiency of regional expenditure.